2013
DOI: 10.1017/s0007114513003681
|View full text |Cite
|
Sign up to set email alerts
|

DHA suppressesPrevotella intermedialipopolysaccharide-induced production of proinflammatory mediators in murine macrophages

Abstract: Several reports have indicated that dietary intake of DHA is associated with lower prevalence of periodontitis. In the present study, we investigated the effect of DHA on the production of proinflammatory mediators in murine macrophage-like RAW264.7 cells stimulated with lipopolysaccharide (LPS) isolated from Prevotella intermedia, a pathogen implicated in inflammatory periodontal disease, and its mechanisms of action. LPS was isolated from lyophilised P. intermedia ATCC 25 611 cells using the standard hot-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…The clustering of gut microbiota profiles by peer group is consistent with our first experiment showing that microbiotic dissimilarity within a group decreased by two weeks after group formation. Microbial convergence within a group would also be in keeping with reports of similar microbial profiles among members of the same household, for farm animals in a shared pen, and even between children and their pet companion animals (5761). Cohousing and cohabitation effects on the microbiota have also been noted in other rodent and primate studies (79).…”
Section: Discussionsupporting
confidence: 65%
“…The clustering of gut microbiota profiles by peer group is consistent with our first experiment showing that microbiotic dissimilarity within a group decreased by two weeks after group formation. Microbial convergence within a group would also be in keeping with reports of similar microbial profiles among members of the same household, for farm animals in a shared pen, and even between children and their pet companion animals (5761). Cohousing and cohabitation effects on the microbiota have also been noted in other rodent and primate studies (79).…”
Section: Discussionsupporting
confidence: 65%
“…In addition, P. intermedia LPS has unique chemical and immunobiological characteristics considerably different from those of the classical LPSs from Escherichia coli and Salmonella species [4143]. Previous studies have shown that P. intermedia LPS induced several mediators of inflammation in human dental pulp cells [8, 9], murine macrophages [44], and bone cells [45] and demonstrated inflammatory responses in mice [46]. Our data show for the first time that LPS from P. intermedia would be able to upregulate the danger signals HMGB1 and RAGE in human dental pulp inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this inflammatory state triggers the secretion of macrophage chemoattractant protein (MCP)-1 by macrophages, which can either sustain a macrophage-like phenotype in undifferentiated precursor cells or diminish the ability of adipocytes to further expand and store lipids, thus supporting a deleterious "vicious cycle" (7,8). Some recent studies reported that specific FA, such as saturated fatty acids (SFA) (9,10), monounsaturated fatty acids (11) and n6-polyunsaturated fatty acids (PUFA) (12) are involved in the pathophysiology of inflammation during obesity (1,2,13,14). In fact, a fat diet rich in SFA likely enhance circulating biomarkers of (pro) inflammation in health individuals (10), and in vitro studies showed that macrophages exposed to SFA increased pro-inflammatory gene expression and cytokine secretion, such as TNF-α and IL-6, and the chemokine CXCL1/KC (9).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies reported that specific FA, such as saturated fatty acids (SFA) (9,10), monounsaturated fatty acids (11) and n6-polyunsaturated fatty acids (PUFA) (12) are involved in the pathophysiology of inflammation during obesity (1,2,13,14). In fact, a fat diet rich in SFA likely enhance circulating biomarkers of (pro) inflammation in health individuals (10), and in vitro studies showed that macrophages exposed to SFA increased pro-inflammatory gene expression and cytokine secretion, such as TNF-α and IL-6, and the chemokine CXCL1/KC (9). A MUFA-enriched high-fat diet (HFD) reverted inflammation-mediated insulin resistance and adipose tissue dysfunction when compared with SFA-fed mice (14).…”
Section: Introductionmentioning
confidence: 99%